Start by calculating the first derivative of f(x) - use the quotient rule
d/dx(f(x)) = ( [d/dx(x^2)] * (x^2 + 3) - x^2 * d/dx(x^2 + 3))/(x^2 + 3)^2
f^' = (2x * (x^2 + 3) - x^2 * 2x)/(x^2 + 3)^2
f^' = (color(red)(cancel(color(black)(2x^3))) + 6x - color(red)(cancel(color(black)(2x^3))))/(x^2 + 3)^2 = (6x)/(x^2 + 3)^2
Before calculating the second derivative, find the critical points of the function by having f^' = 0. These points will help you determine the local minimum and local maximum.
(6x)/(x^2 + 3)^2 = 0 <=> 6x = 0 => x = color(green)(0) -> critical point
To determine where the function is increasing and where it's decreasing, examine the sign of the first derivative around the critical point x=0.
Since the numerator of f^' will always be positive, the sign of the first derivative will be determined by the numerator.
This means that you have 6x<0 for x<0, so the function is decreasing on (-oo,0).
Likewise, because 6x>0 for x>0, the function is increasing on (0, oo).
Now calculate the second derivative - use the quotient and the chain rules
d/dx(f^') = ([d/dx(6x)] * (x^2 + 3)^2 - 6x * d/dx(x^2 + 3)^2)/[(x^2+3)^2]^2
f^('') = (6 * (x^2 + 3)^color(red)(cancel(color(black)(2))) - 6x * 2 * color(red)(cancel(color(black)((x^2+3)))) * 2x)/(x^2+3)^color(red)(cancel(color(black)(4)))
f^('') = (6 *(x^2 + 3) - 24x^2)/(x^2 + 3)^3
f^('') = (-18x^2 + 18)/(x^2 + 3)^3 = -(18 * (x^2-1))/(x^2 + 3)^3
You can determine the local minimum and local maximum of the function by using the second derivative test, which tells you that if you have c as a critical point of f(x), then the sign of f^('')(c) will tell you
So, your critical point is c=0, which means that you have
f^('')(0) = -18 * (0^2 -1)/(0^2 + 3)^3
f^('')(0) = -18 * ((-1))/27 = 18/27 = 2/3
The point (0, f(0)) will be a local minimum. Moreover, the point (0, f(0)) will be an absolute minimum as well, since
f(x) = x^2/(x^2 + 3) > 0,(AA) x !=0 on (-oo,oo)
To determine where the function is concave up and where it's concave down, analyze the behavior of f^('') around the Inflection points, where f^('')=0.
f^('') = -(18(x^2-1))/(x^2 + 3)^2=0
This implies that
-18(x^2-1) = 0 <=> x^2 = 1 => x = +-1
Now you're going to see what the sign of the second derivative is for the intervals
It's clear that f^('') will be negative on this interval, so f will be concave down.
On this interval, f^('') will be positive, since (x^2-1) will be negative. As a result, f will be concave up.
Once again, f^('') will be negative for this interval, so f will be concave down.